Robust contact tracing and screening needed for leprosy control and protection of vulnerable children - Khyathi Reddy Pilaka; Michael Sukumar Pallapati; Zakaraiah Jaladi; Kumar Ebineshan (Iranian Journal of Microbiology)
Leprosy in children is considered as an indicator of active disease transmission in the community. We report about a seven-year-old male from Telangana, India, with anesthetic skin lesions and familial leprosy history. Clinical examination revealed multiple, dry, scaly, hypopigmented, well-defined, raised punched out anesthetic skin lesions all over the body with both ulnar nerves enlarged. On clinical and laboratory examination, the child was diagnosed with borderline-borderline (BB), multibacillary (MB) leprosy, and Type-1 reaction. The child received a weight-adjusted MB multidrug therapy regimen and corticosteroids for type-1 reactions. This case emphasizes the need for contact tracing and screening for early diagnosis of child leprosy to prevent complications like leprosy reactions which are the risk factors for disability.